A Study on Legislative Responses and Judicial Perspective of Data Protection in India: Examining legislative and judicial perspectives on data protection in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
An solid data security and privacy framework is necessary for a nation's advancement. As aconsequence of corporations' inclination to collect increasingly sensitive and personal information, thishas occurred. Nations like the United States and the United Kingdom have recognised India as a centre foroutsourcing. These countries believe that citizens have the right to their own privacy and the right to havetheir personal information kept private and secure. In order to stay competitive, India must thus maintaina solid legal and regulatory framework for data security and privacy. This research examines the legaland legislative responses to data protection in India from a judicial and legislative perspective.